Pemodelan Harga Saham Menggunakan Arma-Garch - Dwi Sulistiowati; Maya Sari Syahrul; Iswan Rina (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2022)
Autoregressive Conditional Heteroscedasticity (ARCH) and Generalized Autoregressive Conditional Heteroskedasticity (GARCH) models were used for modeling with heteroscedasticity data. This study aims to determine the time series model on the stock price data of PT Triputra Agro Persada Tbk. (TAPG) with modeling ARMA, ARCH and GARCH. Based on the smallest Akaike Information Criterion (AIC) and Schwarz Criterion (SC), it shows that the ARMA(1,0)-GARCH(2,1) model is the best model for predicting the value of TAPG stock prices.